Penguatan Ekonomi Mikro: Pendampingan Bagi Pedagang Tempe dan Tahu dalam Mengembangkan Usaha di Wilayah Palembang - Marsinah Marsinah; Sri Dweni Astuti; Fitria Marisya; Jamilah Jamilah (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2025)
This activity aims to increase the business capacity of MSME actors through business management training, digital marketing, and technical assistance. The activity was held on April 16, 2025 at the Tempe Tofu Production Center, Jl. Macan Lindungan No.43 Bukit Kecil Village, Ilir Barat 1 District, Palembang, with a total of 20 traders. The methods used include initial observation, program socialization, financial management training, social media workshops, and marketing strategy assistance. The results showed that 80% of participants began to use digital platforms for promotion, 7 traders succeeded in preparing capital assistance proposals, there was an improvement in product packaging, and the formation of the "Tahu Tempe Mandiri" business group. This program has a positive impact on increasing turnover and market access. For sustainability, it is recommended that there be further training and collaboration with relevant agencies.